Penjaminan Mutu Internal Perguruan Tinggi - Halimatus Sakdiyah (INSANIA : Jurnal Pemikiran Alternatif Kependidikan, 2018)
Abstract: There are many higher education executives in Indonesia that still carry out fewer learning activities under the quality standars, so ultimately the credibility of higher education is still not satisfying the stakeholders. A college should be able to make internal quality standards beyond the minimum quality standards made by the National Education Standards Agency (BSNP). Currently, quality assurance in the form of systems development and the astablishment of the agency has not been done much in the college. The role of internal quality assurance for higher education is also still inadequate to boost quality improvement. This is where the need for internal quality assurance agency in college that aims to repair and improve the quality of higher education on an ongoing basis. Keywords: Internal Quality Assurance and Higher Education.